Seroepidemiology of coxsackievirus B5 in infants and children in Jiangsu province, China - Fan Gao; Lianlian Bian; Xiaotian Hao; Yalin Hu; Xin Yao; Shiyang Sun; Pan Chen; Ce Yang; Ruixiao Du; Jingxin Li; Fengcai Zhu; Qunying Mao; et al. (Taylor & Francis Group, 2018)
Coxsackievirus B5 (CV-B5) is associated with various human diseases such as viral encephalitis, aseptic meningitis, paralysis, herpangina, and hand, foot and mouth disease (HFMD). However, there is currently no effective vaccine against CV-B5.The seroepidemiologic characteristics of CV-B5 remained unknown. A cohort study was carried out in 176 participants aged 6-35 months from January 2012 to January 2014. The serum samples were collected and tested for CV-B5 neutralizing antibodies (NtAbs) four times during these two years. The confirmed enterovirus cases were recorded through the surveillance system, and their throat or rectal swabs were collected for pathogen detection. According to the changes of CV-B5 NtAbs, two CV-B5 epidemics were detected among these participants during the two-year follow-up. Sixty-seven cases out of all participants had seroconversion in CV-B5 NtAbs. During the first epidemic from March 2012 to September 2012, CV-B5 seropositivity rate increased significantly (6.8%, 12/176 vs. 21.6%, 38/176, P = 0.000). The seroconversion rate and geometric mean fold-increase (GMFI) were 18.2% (32/176) and 55.7, respectively; During the second epidemic from September 2012 to January 2014, CV-B5 seropositivity rate also increased (21.6%, 38/176 vs. 38.6%, 68/176, P = 0.000), and the seroconversion rate and GMFI were 19.9% (35/176) and 46.5, respectively. Only one case had CV-B5 associated HFMD during the two-year follow-up, and CV-B5 from the throat swab isolate was GI.D3 subtype, which belonged to the major pandemic strain in mainland China. CV-B5 infection was common in infants and children in Jiangsu province, China. Therefore, it's necessary to strengthen the surveillance on CV-B5 and to understand the epidemic characteristics of CV-B5 infection.